Mentha rotundifolia (L.) Huds. aqueous extract attenuates H2O2 induced oxidative stress and neurotoxicity - Boualam, Khadija; Bouhaddou, Nezha; Sobeh, Mansour; Tabyaoui, Mohamed; Taghzouti, Khalid (Frontiers in Neuroscience, 2023)
Introduction Oxidative stress plays a causal role in neurodegenerative diseases. The aim of this study is to evaluate the antioxidant and neuroprotective effects of Mentha rotundifolia (L.) Huds (M. rotundifolia), a widely used Moroccan plant in traditional medicine. Methods The chemical composition of M. rotundifolia aqueous extract was analyzed by liquid chromatography coupled to mass spectrometry (LC-MS). 2,2-diphenyl 1-picrylhydrazyl (DPPH) and 2,2′-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS+) assays were used to assess its in vitro antioxidant activity. H2O2 was utilized to induce oxidative stress and neurotoxicity in vivo. Behavioral changes were evaluated using Open Field, Y-maze and Rotarod tests. Hyperalgesia was assessed using the tail immersion test. Results and discussion The LC-MS/MS analysis revealed high content of kaempferol glucuronide (85%) at the extract. IC50 values of the DPPH and ABTS were 26.47 and 41.21 μg/mL, respectively. Pre-treatments with M. rotundifolia extract attenuated the behavioral changes induced by H2O2. In addition, the latency of tail withdrawal increased significantly in the treated groups suggesting central analgesic effect of M. rotundifolia extract. Moreover, the extract attenuated the deleterious effects of H2O2 and improved all liver biomarkers. The obtained results suggested that M. rotundifolia had remarkable antioxidant and neuroprotective effects and may prevent oxidative stress related disorders.